Análise filogenética do circovírus suíno tipo 2 no Brasil - Juliana Amalia Fonte Boa do Nascimento (2009)
The aims of this work were to study the genetic diversity of the porcine circovirus type 2 (PCV-2) and to identify and discriminate genogroups based on the ORF3 sequence from PCV-2 from animals with clinical signs of the Porcine Circoviruses Associated Disease (PCVAD). And also the study of the correlation between histopatologic lesions observed in animals with a compatible clinical signs of PCVAD and Porcine Respiratory Disease Complex (PRDC). The sampling consisted of lymphoid and non lymphoid tissue pools from swines from farms of the following Brazilian states: Mato Grosso, Goiás, Minas Gerais, Espirito Santo, São Paulo, Paraná, Santa Catarina and Rio Grande do Sul. The macroscopic lesions were described by the necropsy and lymphoid and non-lymphoid tissue fragments were submitted to isolation and identification of bacterial co-infections, virus titration as well as histopathological diagnosis was performed using hematoxylin-eosin stain. The main pathological findings were lymphoid follicles with lymphocyte depletion and histiocytic cell infiltration, bronco-interstitial pneumonia, interstitial nephritis with multifocal lymphohistiocytic inflammatory infiltrates. The microscopic lesions were classified in discrete, moderate and severe, evaluated with the viral load on tissue pool and associated with the phylogenetic analysis of the PCV2 ORF3 gene. The macroscopic and microscopic lesions and the frequence of main pathological findings were compatible with the description of animals with PCVAD clinical signs. The microbiological evaluation of the tissues samples recognized 6% of Bordetella bronchiseptica, 7% of Escherichia coli, Actinobacillus pleuropneumoniae and Pasteurella multocida type D, 10% of Haemophilus parasuis, 20% of Streptococcus suis and 23% of Pasteurella multocida type A. The relation between the histopatologic findings and the co-infections suggested association between the PCV-2 and PRDC, suggesting a synergic effect in the host immunosuppression by the microorganisms. All samples were submitted to the polymerase chain reaction (PCR) of ORF2 and ORF3 genes from PCV-2, PCR products were then purified and sequenced for phylogenetic analysis. A nucleotide and amino acid alignment was performed and the phylogenetic tree was constructed using the Neighbor Joining (NJ). The results showed that the circulating PCV-2 in all samples belonged to group 1, sub-groups 1A and 1B. The frequency of the subgroups was markedly different since 88.5% of the samples were classified as subgroup 1A, and only 11.5% belonged to subgroup 1B. The ORF3 sequence alignment enabled the divide of samples in three genogroups: SG1, SG2 and SG3. The selective pressure and phylogeographic analysis were also performed for ORF3. The selective pressure analysis showed positive selection in ORF3 gene at positions 41, 102 and 104 (p0.95%). The phylogeographic study enabled the distribution of the samples on SG1, SG2 and SG3 genogroups and correlations. The SG1, SG2, SG3 genogroups were distributed within 14 haplotypes. The SG3 was grouped sequences from the nine states and was considered to be the ancestral haplotype due its wide dispersion. The possibility of different variants circulating in the same farm at distinct dates was also evaluated. The detection of SG1, SG2 and SG3 genogroups in samples collected at distinct times from the same farm indicates the presence of PCV-2 variants circulating in different management systems in the Brazilian swine farms. The relation of the ORF3 genogroups and the classification of the PCV-2 demonstrated that SG1 and SG2 belonged to the sub-group 1B while the SG3 was grouped in 1A.